Negotiation, collaboration and conflict in ancient and medieval communities
1 online resource
Keywords: "Focusing on forms of interaction and methods of negotiation in multicultural, multi-ethnic and multilingual contexts during Antiquity and the Middle Ages, this volume examines questions of social and cultural interaction within and between diverse ethnic communities. Toleration and coexistence were essential in all late antique and medieval societies and their communities. However, power struggles and prejudices could give rise to suspicion, conflict and violence. All of these had a central influence on social dynamics, negotiations of collective or individual identity, definitions of ethnicity, and the shaping of legal rules. What was the function of multicultural and multilingual interaction: did it create and increase conflicts, or was it rather a prerequisite for survival and prosperity? The focus of this book is society and the history of everyday life, examining gender, status and ethnicity, and the various forms of interaction and negotiation"--